2017
DOI: 10.1007/s11600-017-0075-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes of flood risk on the northern foothills of the Tatra Mountains

Abstract: The present paper reviews selected outcomes of the FLORIST project devoted to flood risk in the region of the northern foothills of the Tatra Mountains in Poland and summarizes novel results. The project encompassed theoretical, field, and modeling work. It was focused around observation-based hydroclimatology; projections for the future; dendrogeomorphology; as well as influence of transport of large wood on fluvial processes. The project improved understanding and interpreting changes in highflow frequency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Meresa et al ( 2017 ) indicated a positive trend of different indices derived from hydroclimatic projections for most of Polish and Norwegian catchments. In the light of climate changes having been taking place for some time, the analysis of characteristic flow trends for rivers has become an essential factor in the effective water management planning in a given region (Kundzewicz et al 2017 ; Walega et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meresa et al ( 2017 ) indicated a positive trend of different indices derived from hydroclimatic projections for most of Polish and Norwegian catchments. In the light of climate changes having been taking place for some time, the analysis of characteristic flow trends for rivers has become an essential factor in the effective water management planning in a given region (Kundzewicz et al 2017 ; Walega et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the uncertainty in flood inundation modeling can be categorized into seven major types: (1) topographic data, (2) hydrologic data, (3) data for preliminary estimation of roughness, (4) method applied for final roughness calibration, (5) method applied for estimation of maximum flows, (6) structure of the applied model and (7) transition of the model results to the maps (e.g., Refsgaard and Storm 1990;Cook and Merwade 2009;Calenda et al 2009;Liu and Merwade 2018). Some of the above-listed elements become less uncertain due to the development of the technology, e.g., increasing accuracy and resolution of LIDAR data for DEM elaboration (e.g., Gilles et al 2012;Sampson et al 2012;Walczak et al 2013;Laks et al 2017), involvement of satellite and remote sensing data (e.g., Jung et al 2014;Arseni et al 2017), elaboration of more detailed databases on flood events (e.g., Kundzewicz et al 2017) and broader availability of more accurate hydraulic models (e.g., Szydłowski et al 2013;Gąsiorowski 2013;Brunner 2016a;Kolerski 2018). A specific problem is the uncertainty related to the channel and floodplain roughness (e.g., Dimitriadis et al 2016;Pappenberger et al 2008;Engeland et al 2016;Liu and Merwade 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The papers published under this Topical Issue can be classified into those describing observed changes in flow patterns in catchments (Kundzewicz et al 2017b;Somorowska 2017), papers presenting changes in the trends of future flow projections Piniewski et al 2017). The paper by Doroszkiewicz and Romanowicz (2017) presents issues related to adaptation to floods under future climatic conditions.…”
mentioning
confidence: 99%
“…There are two papers in this issue that directly deal with the observed flow patterns (those by Somorowska 2017; Kundzewicz et al 2017b). Somorowska (2017) describes the trends in flow regime in a low-land catchment, Lasica.…”
mentioning
confidence: 99%
See 1 more Smart Citation